Structural violence by state: India’s indirect endorsement towards the three decades-long sex-selective abortion (SSA) - Siti Hilya Nabila (Interaction, Community Engagement, and Social Environment, 2023)
This research aims to contribute to the debate on structural violence by state, by explaining how pro-human rights policies ironically can be produced, implemented, and used by state as instruments to perpetrate human rights violations. By using the concept of structural violence, this research is offered that the Indian government has allowed the practice of female foeticide in India to continue to occur among India's poor women from 1994 to 2014 through the implementation of anti-sex-selective abortion (anti-SSA) policy: Pre-Course Pre-Natal Diagnostic Technique (PCPNDT) Act of 1994. This study attempts to investigate how the Indian government perpetuates structural violence by producing, implementing, and maintaining this provenly ineffective human rights policy by using qualitative method and secondary data. This paper finds that the neglect of intersectionality analysis in the design of the policy is a form of structural violence conducted by the Indian government. In this case Indian government has implemented segmentation and marginalization in order to allow the continuation of female foeticide among its poor women for the last three decades. Generally, the neglect of intersectionality analysis in the policy represents the government’s support towards the high preference of boys and extremely low preference of girls, especially poor girls and girls from the outcast. Although the anti-SSA policy has been in place since 1994, data on sex ratios at birth from 1982 to 2014 show that the gap between the births of girls and boys is becoming more and more imbalanced. Various researchers found that the policy was not effective in resolving the problem of sex ratios due to its poor implementation management that caused difficulties in arresting the perpetrators of SSA and regulating the practice up to the grassroots level. However, this paper argues that poor management is not the main cause the policy is failing. This research finds that the Indian government deliberately excludes & does not recognize the identity of poor & outcast women in the policy design. In fact, the practice of SSA is mostly carried out by women in these segments.